Rethinking the Notion of Universality in Judaism and its Implications - Sandberg, Ruth (Studies in Christian-Jewish relations, 2017)
The Vatican document, The Gifts and the Calling of God Are Irrevocable, insists that the covenant between God with Israel has never been revoked, yet at the same time asserts that there is universal salvation for the world through Christ, that Christ is also the Redeemer of the Jews and that Jews and Christians are ultimately united in Christ. What is termed universality in this document is essentially triumphalist universality, in which salvation is the universal goal open to everyone, but ultimately through Christ. Yet this triumphalist universalism has its roots in the Hebrew Bible itself, in which the salvation of the world lies in everyone accepting the specific monotheism of Israel, and this triumphalist view continues in rabbinic Judaism as well. Nevertheless, the seeds of an inclusive universalism, in which all people are worthy in the eyes of God whether they part of Israel or not, does appear in the Tanakh and in rabbinic sources, and this inclusive universalism can serve as a model for Jews and Christians today.